Jazf1 acts as a regulator of insulin‐producing β‐cell differentiation in induced pluripotent stem cells and glucose homeostasis in mice. (23rd April 2021) - Park, Si Jun; Kwon, Wookbong; Park, Song; Jeong, Jain; Kim, Dongjun; Jang, Soyoung; Kim, Si‐Yong; Sung, Yonghun; Kim, Myoung Ok; Choi, Seong‐Kyoon; Ryoo, Zae Young
Abstract : Genetic susceptibility of type 2 diabetes and Juxtaposed with another zinc finger protein 1 (Jazf1) has been reported; however, the precise role of Jazf1 in metabolic processes remains elusive. In this study, using Jazf1‐knockout (KO)‐induced pluripotent stem cells (iPSC), pancreatic beta cell line MIN6 cells, and Jazf‐1 heterozygous KO (Jazf1 +/− ) mice, the effect of Jazf1 on gradual differentiation was investigated. We checked the alterations of the genes related with β‐cell specification, maturation, and insulin release against glucose treatment by the gain and loss of the Jazf1 gene in the MIN6 cells. Because undifferentiated Jazf1‐KO iPSC were not significantly different from wild‐type (WT) iPSC, the size and endoderm marker expression after embryoid body (EB) and teratoma formation were investigated. Compared to EB and teratomas formed with WT iPSC, the EB and teratomas from with Jazf1‐KO iPSC were smaller, and in teratomas, the expression of proliferation markers was reduced. Moreover, the expression of the gene sets for β‐cell differentiation and the levels of insulin and C‐peptide secreted by insulin precursor cells were notably reduced in β‐cells differentiated from Jazf1‐KO iPSC compared with those differentiated from WT iPSC. A comparison of Jazf1 +/− and WT mice showed that Jazf1 +/− mice had lower levels of serum insulin, pancreatic insulin expression, and decreased pancreatic β‐cell size, which resulted in defects in the glucose homeostasis. These findings suggest that Jazf1 plays a pivotal role in the differentiation of β‐cells and glucose homeostasis. Abstract : In this study, we uncover the essential role of Juxtaposed with another zinc finger protein 1 (Jazf1) in the differentiation of β‐cells and glucose homeostasis. Induced pluripotent stem cells generated from mice harboring a knockout mutation of Jazf1 led to a reduction in size and capacity for differentiation into insulin‐producing β‐cells as well as a decrease in the insulin produced by the β‐cell mass. In addition, insulin resistance was observed in Jazf1 +/− mice, which disrupted glucose homeostasis.